Hollow fiber composite membranes engineered via the combination of "anionic crosslinking and in-situ biomineralization" for dye removal. (5th October 2022) - Bian, Lei; Wei, Qianqian; Li, Jianxin; Zhang, Jing; Qin, Shuhao; Yang, Jingkui; Cui, Zhenyu
Graphical abstract: Highlights: Hybrid layer was in situ constructed on hollow fiber membrane outer surface. Relationship between anions and compactness of separation layers was expounded. Minerals improve hydrophilicity of membrane and benefit water penetration. The minerals are combined by anionic crosslinking to avoid falling off. The membrane indicated excellent dye rejection, stability and acid resistance. Abstract: In this study, hollow fiber composite membranes were prepared by fabricating a hybrid separation layer on hollow fiber membranes outer surface through the combination of "anionic crosslinking and in-situ biomineralization". The relationship between anions (molecular weight, Mw and functionality, fu ) and the compactness of separation layers were analysed. The mode of in-situ biomineralization on surface, the formation and evolution of the hybrid layers were discussed. Using the strategy of anionic crosslinking and in-situ biomineralization, the compactness and filtration accuracy could be effectively enhanced, and the hydrophilicity of membrane surface was greatly improved. Dyes with low Mw, such as methyl orange (327 g mol −1, 99.6 %, 21.2 L m –2 h −1 ) and methylene blue (319 g mol −1, 99.2 %, 21.9 L m –2 h −1 ), can be rejected precisely while maintaining a high permeate flux. In addition, owing to the better acid resistance of the hybrid separation layer and the good adhesion between the separation layer and substrate, the membrane exhibited excellent chemical stability, long-term separation stability, and anti-fouling capacity. This study provides facile method for building separation layers with hybrid structures on hollow fiber membranes and a novel idea for designing hollow fiber composite membranes to separate dyes from water.